The species of genus Staelia (Rubiaceae) Paraguay, a new species and new synonymous - Salas, Roberto Manuel (2010)
A new species of the genus Staelia is described and illustrated from the Boquerón department of Paraguay: S. nelidae. In total, three Staelia species have been recognized for Paraguay. Staelia hassleri is proposed as a new synonym of the widespread S. thymoides. A key to distinguish the new species and the remaining taxa from Paraguay is also provided. The pollen and seed morphology are also analyzed and its relevance is discussed.